(untitled) (Biological Sciences - PJSIR, 2023)
Generation of genetically modified (GM) crops is quickly expanding around the world. The quality assessment of these harvests is a vital issue and this droves of the administrative specialists to execute an arrangement for the endorsement to develop and use GM to create and produced an interest in scientific techniques equipped for identifying GM crops. The GM crops have added to the effective fuse of various attributes by presenting transgenes, e.g. Bacillus thuringiensis (Bt) insecticidal qualities, in various yield species. Dependable recognition strategies are vital for the identification of un-approved GMOs. According to James in (2018), the planting area of global genetically modified (GM) crops has reached 1.971 billion hectares, a 100-fold increase from the 1.7 million hectares in 1996. GM crops give financial, natural, well-being, social advantages to both little and huge agriculturists in creating and mechanical motions. A quick and simple immuno-chromatographic (ICS) test was set up which is modest compact and simple to utilize. The ICS is a semi-quantitative method for screening and semi measurement new proteins presented through hereditary change of plants. Strip assay developed first time in Asia and used it for assessment of several Bt transformed crop plants for insecticidal quality. The cultivation of GM crops is important and more traits are emerging and more area is being planted with GM varieties. The release of GM crops products in the markets worldwide has increased regulatory need to monitor, verify the presence and amount of GM varieties in crops and products. In 2017, global GM area reached to 189 million hectares, which indicates high adoption rate of GM crops by farmers and reflects its consistent performance. More than 8 million farmers are benefiting from it. About 90% of the beneficiary farmers are resource-poor farmers from developing countries, whose increased incomes from biotech crops contributed to alleviation of poverty. So, developed the quick strip assay, utilized it for assessment of Bt-ICP crop plants.